Challenges of the social and structural identity in the Middle East )Iraq as a model( - misanjas, misanjas; Radhi Kadhim, Yousif ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Middle East is a complex geographical region, and the events of the past 100 years have affected the world. Although various issues in the regional, political, economic and social fields of the Middle East have led to large-scale conflicts, the conflict today is taking place on a strategic scale and based on the interests of the powers in the region. Since the events of 9/11, new factors such as al-Qaeda terrorism, regional crises in Afghanistan, Iraq, Syria and Lebanon, along with the growing role of Shiites in the regional power structure and, of course, nuclear Iran, have led to linking the politics and security of the Middle East with international security, and turning Middle East issues into International and public issues. This research reviews the conflicts and challenges in the Middle East region, with a study of the case of Iraq.